Teaching English as an Additional Language or Dialect to Young Learners in Indigenous Contexts - Steele, Carly; Wigglesworth, Gillian (Routledge, 2018)
This chapter explores the diversity of Indigenous contexts and their differing learning needs related to Standard Australian English. It discusses some of the key theories of language learning and pedagogical approach within these contexts and how these have been applied to classroom practice in Indigenous contexts. The chapter highlights current local and mainstream assessment practices used with this group of learners, and the implications for doing so. It provides some background on the varieties of language teachers may expect to encounter when working in regional and remote communities. The chapter presents examples and discusses a range of ideas about how teachers can engage with the curriculum and the context, as well as thoughts about the assessment of the children's language. It expresses that to improve educational outcomes, it is essential for schools to incorporate both culture and literacy development in the first language. It is also important that there is community involvement in bilingual schooling.